Rebel governance and political participation - Abbey Steele; Michael Weintraub (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
Rebels, militias, and criminal groups all govern civilians. Governing strategies adopted by armed groups during civil war likely influence citizens' post-conflict political participation, with consequences for democratic politics. We theorize that an armed group's position relative to the state (anti-state or pro-state) and governing ideology (sharing governing responsibilities with local institutions or destroying them to govern centrally) interact to influence citizens' later choices about political participation. We test our argument with an original household survey of 12,000 households from war-affected communities in Colombia. Contrary to expectations, having experienced governance by either anti-state groups or pro-state paramilitaries increased participation in formal and informal political channels when compared to those not having experienced armed group rule. We explore potential explanations for these unexpected results and demonstrate the importance of studying the long-run political effects of wartime governance by armed groups.
Keywords: D74; D71; D72; 330; armed group governance; political participation; civil war; Colombia; household surveys